Ab initio molecular dynamics investigation of the proton conductivity and dynamics behavior of hydrous ringwoodite under high temperatures and pressure - SiYu Zhou; DaoHong Liu; ChuanYu Zhang; XuBen Wang; Li Song (Earth and Planetary Physics, 2025)
The electrical conductivity of minerals under extreme conditions is governed by their variations in composition and structure. Constitution water, which is present in various polymorphic phases of olivine, can significantly enhance electrical conductivity under mantle pressure−temperature conditions, therefore playing a key role in proton transport. Despite this, the conductive mechanisms in hydrous olivine, particularly in hydrous ringwoodite, and the dynamic behavior of hydrogen at elevated temperatures, remain poorly understood. In this study, we investigated the proton conduction mechanisms in hydrous ringwoodite through first-principles calculations. Several hydrous models were considered, and ab initio molecular dynamics (AIMD) simulations were employed to simulate hydrous configurations at high temperatures. Calculations based on density functional perturbation theory (DFPT) and vibrational density of states (VDOS) analyses were conducted to probe the stability of hydrous structures, and investigate the dynamic behavior of internal hydrogen. Our results indicate that hydrogen trapped in Mg2+ and Fe3+ defects exhibits significantly higher mobility than hydrogen trapped in Si4+ defects. At elevated temperatures, we observed the ionization of hydrogen from cationic defects, leading to high and highly anisotropic proton conductivity along the [100] crystallographic direction. This thermal ionization-induced anisotropic conductivity is consistent with experimental observations of olivine single crystals. Finally, the conductivity of the 0.79 wt% hydrous ringwoodite structure was found to range from 10−0.3 to 100.4 S/m, the 1.19 wt% structure ranged from 100.4 to 100.9 S/m in the transition region, and the 1.62 wt% structure exhibited conductivity ranging from 100.7 to 101.2 S/m. These results are in excellent agreement with prior experimental data, providing further insight into the proton conduction mechanisms of hydrous olivine under extreme mantle conditions.